2021
DOI: 10.1007/s00414-021-02656-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the third molar maturity index (I3M) between left and right lower third molars to assess the age of majority: a multi-ethnic study sample

Abstract: The diagnostic accuracy of the I 3M to assess the legal age of 18 years has already been tested in several specific-population samples. The left lower third molar has been extensively used for discriminating between minors and adults. This research aimed to compare the usefulness of lower third molar maturity indexes, from both left and right side (I 3M L and I 3M R), in samples originating from four distinct continents in order to examine possible differences in their accuracy values. For this purpose, a samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…The non-LATAM countries with the greatest collaborations were Russia (15 studies), the UK (10 studies), and Italy (8 studies). Two publications involved large multi-ethnic studies to validate the third molar maturity index in European, Asian (Angelakopoulos et al, 2021) and African (Angelakopoulos et al, 2023) countries, including Brazil, Chile, Peru, and the Dominican Republic. The LATAM researcher with the highest productivity was Prof. Ademir Franco, with declared affiliations to the São Leopoldo Mandic School of Dentistry (Campinas, Brazil), the Department of Imaging and Pathology, Forensic Odontology, KU Leuven (Leuven, Belgium), the Center of Forensic and Legal Medicine and Dentistry, University of Dundee (Scotland, UK), and the Department of Therapeutic Stomatology, Sechenov University (Moscow, Russia).…”
Section: Resultsmentioning
confidence: 99%
“…The non-LATAM countries with the greatest collaborations were Russia (15 studies), the UK (10 studies), and Italy (8 studies). Two publications involved large multi-ethnic studies to validate the third molar maturity index in European, Asian (Angelakopoulos et al, 2021) and African (Angelakopoulos et al, 2023) countries, including Brazil, Chile, Peru, and the Dominican Republic. The LATAM researcher with the highest productivity was Prof. Ademir Franco, with declared affiliations to the São Leopoldo Mandic School of Dentistry (Campinas, Brazil), the Department of Imaging and Pathology, Forensic Odontology, KU Leuven (Leuven, Belgium), the Center of Forensic and Legal Medicine and Dentistry, University of Dundee (Scotland, UK), and the Department of Therapeutic Stomatology, Sechenov University (Moscow, Russia).…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that sex (g, males = 1, females = 0), the variables s (the sum of normalised measurements) and N0, and the first-order interaction between them contributed substantially to the fit (p < 0.001). To maintain a consistency with the previous approaches [2,9], the value of x5 (the ratio between apex width and height of the second premolar) was considered despite a low level of prediction (Table 2). All these variables were included in the regression model, yielding the following multiple linear regression formula (R = 0.952; adjusted R 2 = 0.905): Age = 10.372 + 0.469 g + 0.810 N0 − 1.079 s − 0.398 s•N0 − 0.326 × 5…”
Section: Resultsmentioning
confidence: 99%
“…In growing children, different biological indicators correlate better with the age of an individual [1]. However, the development of permanent teeth is more reliable than other indicators of age, such as the hand-wrist bones maturation, as the dental maturation and development is controlled more by genes than by environmental factors [1,[7][8][9][10]. The dental age assessment methods are based on the identification of the stages of mineralisation in radiographic images, followed by their comparison with the standard stage to estimate the approximate age range (qualitative methods).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, only one side was analysed considering the symmetry of dental traits between right- and left-side measurements as demonstrated by previous research [ 23 , 36 ].…”
Section: Methodsmentioning
confidence: 99%